ПРОТИПУХЛИННИЙ ІМУНОГЕННИЙ ПОТЕНЦІАЛ ОНКОЛІТИЧНИХ ПЕПТИДІВ: ОСТАННІ ДОСЯГНЕННЯ ТА НОВІ ПЕРСПЕКТИВИ - KHRANOVSKA, N.; SKACHKOVA, O.; GORBACH, O.; SEMCHUK, I.; SHVETS, Yu.; KOMAROV, I. (PH Akademperiodyka, 2024)
Oncolytic peptides are derived from natural host defense peptides/antimicrobial peptides produced in a wide variety of life forms. Over the past two decades, they have attracted much attention in both basic research and clinical applications. Oncolytic peptides were expected to act primarily on tumor cells and also trigger the immunogenic cell death. Their ability in the tumor microenvironment remodeling and potentiating the anticancer immunity has long been ignored. Despite the promising results, clinical application of oncolytic peptides is still hindered by their unsatisfactory bioactivity and toxicity to normal cells. To ensure safer therapy, various approaches are being developed. The idea of the Ukrainian research group was to equip peptide molecules with a "molecular photoswitch" — a diarylethene fragment capable of photoisomerization, allowing for the localized photoactivation of peptides within tumors reducing side effects. Such oncolytic peptides that may induce the membrane lysis-mediated cancer cell death and subsequent anticancer immune responses in combination with the low toxicity to normal cells have provided a new paradigm for cancer therapy. This review gives an overview of the broad effects and perspectives of oncolytic peptides in anticancer immunity highlighting the potential issues related to the use of oncolytic peptides in cancer immunotherapy. We summarize the current status of research on peptide-based tumor immunotherapy in combination with other therapies including immune checkpoint inhibitors, chemotherapy, and targeted therapy.